2019
DOI: 10.1007/s11747-019-00673-7
|View full text |Cite
|
Sign up to set email alerts
|

Categorical versus dimensional thinking: improving anti-stigma campaigns by matching health message frames and implicit worldviews

Abstract: Despite growing applications of social and healthcare marketing to enhance public well-being through anti-stigma campaigns, little research investigates how public stigma surrounding health conditions might limit the outcomes of these campaigns. By drawing on the theory of implicit worldviews, this study identifies reasons for public stigma as well as associated message frames to address these reasons. Study 1a provides evidence that implicit worldviews are relevant to campaign results. Study 1b and Study 2 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Specifically, whilst those participants exposed to continuum beliefs did see someone with experiences of schizophrenia as more similar to themselves and did increase their belief in possible recovery, the type of message did not significantly impact measures of explicit prejudice and discrimination ( 99 ). Similarly, an evaluation of the Time To Change campaign in the UK found that biopsychosocial messages relative to biomedical messages only had an effect on participants' desires for social distance in those who already understood mental illness in dimensional terms ( 100 ).…”
Section: Public Health Campaignsmentioning
confidence: 99%
“…Specifically, whilst those participants exposed to continuum beliefs did see someone with experiences of schizophrenia as more similar to themselves and did increase their belief in possible recovery, the type of message did not significantly impact measures of explicit prejudice and discrimination ( 99 ). Similarly, an evaluation of the Time To Change campaign in the UK found that biopsychosocial messages relative to biomedical messages only had an effect on participants' desires for social distance in those who already understood mental illness in dimensional terms ( 100 ).…”
Section: Public Health Campaignsmentioning
confidence: 99%
“…It has been argued that stigma should be considered a fundamental cause that is associated with health inequalities in a manner similar to socio-economic status and acknowledged as an important determinant of population health and the effectiveness of planned interventions (Hatzenbuehler et al, 2013;Meyer et al, 2020). However, stigma can oftentimes go unrecognized as people who do not have diabetes presume that it is not a stigmatized condition.…”
Section: Introductionmentioning
confidence: 99%
“…47,62 Policy evaluations included the European Union, 5 Australia/France/ Switzerland, 25 Canada, 27 and England/France/Germany Scotland. 29 There were 41 studies that explored obesity-related policy support, which were grouped into the following themes: 25 (61.0%) studies focused on weight bias (e.g., causal attributions of obesity or assigning individual or societal responsibility for obesity), explored in relation to policies focused on the prevention and treatment of obesity; 12 (29.3%) studies focused on antidiscrimination or antibullying weight-based policies that attempted to reduce weight stigma 11,30,38,43,47,48,50,59,60,61,63,65,67 ; of the remaining studies, two (5.1%) covered both causal attribution and antidiscrimination/bullying, 49,62 one study focused on weight-based prejudice, 32 and one on weight stigma in health research and practice. 24 Seven (17.1%) studies evaluated media or news articles (real or fake).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…57,66 3.4.2 | Studies focused on antidiscrimination or antibullying weight-based policies to reduce weight stigma Obesity-related antidiscrimination policies that attempted to reduce weight stigma included laws such as legal protection of people living with obesity (such as that for people with physical disabilities), laws against weight-based discrimination at the general population (i.e., state or federal) and workplace levels, and strategies to address weight-based bullying or victimization at the general population and school levels. 11,43,[48][49][50]62 In general, antidiscrimination measures such as polices and legislation to prohibit weight-based victimization against adults were supported at moderate to high levels (40%-80% 30,38,49 ), with indications that policy support is increasing over time. 11,30,50 Personal characteristics were associated with support for antidiscrimination or bullying policies.…”
Section: Research Question 1: Factors Associated With Policy Supportmentioning
confidence: 99%